Five nights at freddy's : fazbear frights #1: Into the pit - Cawthon, Scott; Cooper, Elley (Scholastic, New York, 2020)
ve Nights at Freddy's fans won't want to miss this pulse-pounding collection of three novella-length tales that will keep even the bravest player up at night . . .What do you wish for most? It's a question that Oswald, Sarah, and Millie think they know the answer to. Oswald wishes his summer wasn't so boring, Sarah wishes to be beautiful, and Millie wishes she could just disappear from the face of the earth. But in the twisted world of Five Nights at Freddy's, their hearts' deepest desires have an unexpected cost. In this volume, Five Nights at Freddy's creator Scott Cawthon spins three sinister novella-length stories from different corners of his series' canon, featuring cover art from fan-favorite artist Lady Fiszi. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddy's fans.
Keywords: Young Adult Fiction; Horror stories; Pizzerias Fiction